Analgesic efficiency of the combination Morphine/Dexketoprofeno versus Morphine/Paracetamol in patients admitted for lower limb surgery (Boletin Médico de Postgrado, 2020)
In trauma and orthopedic surgery, combination of different analgesics and/or analgesic techniques has been used for treatment of pain after surgery. For this reason, a clinical controlled study with 40 patients was performed to test the analgesic efficiency of the combination Morphine/Dexketoprofen versus Morphine/Paracetamol in patients admitted for lower limb surgery at the Service of Orthopedic Surgery and Orthopedics of the Hospital Central Universitario Dr. Antonio María Pineda. Patients were distributed in two groups: Group M/D which received 100 mcg of morphine and 100 mg of Dexketoprofen and Group M/P which received 100 mcg of morphine and 1 gr of paracetamol. Both groups did not show pain in the first 6 hours, 18 hours post surgery 80% of group M/D and 100% of the group M/P showed absence of pain while 24 hours after both groups reported slight pain. Only 35% of patients of group M/D received rescue analgesia; 15 % of group M/D and 5 % of group M/P showed minor adverse effects. The combination Morphine/Dexketoprofen and Morphine/Paracetamol are effective and safe in diminishing post operatory pain in patients submitted for lower limb surgery; nevertheless, the latter does not need rescue analgesia and has minor adverse effects.
Keywords: Analgesia; morphine; traumatology; lower limb; general surgery